P5.081 Analytical Evaluation of the GeneXpert ® CT/NG, the First Genetic Point of Care Assay For Simultaneous Detection of Neisseria Gonorrhoeae and Chlamydia Trachomatis. (13th July 2013) - Tabrizi, S N; Unemo, M; Golparian, D; Twin, J; Limnios, A E; Lahra, M; Guy, R
Abstract : Introduction: New assays for molecular detection of Neisseria gonorrhoeae and Chlamydia trachomatis need to be evaluated for potential false positive and false negative results due to cross reaction with other species, and potential mutations and genetic exchanges with other closely related organisms. Cepheid GeneXpert® CT/NG is the first FDA approved genetic point of care (POC) assay which simultaneously detects C. trachomatis, N. gonorrhoeae and controls for sample adequacy, in less than 90 minutes. Method: This study evaluated the GeneXpert ® CT/NG assay with 372 characterised culture isolates; 111 N. gonorrhoeae isolates (including 3 isolates with N. meningitidis porA sequence), 223 isolates of non-gonococcal Neisseria species, 13 isolates of other species closely related to Neisseria and 25 C. trachomatis strains of different serovars (including LGV and nvCT strains). Results: All C. trachomatis and N. gonorrhoeae isolates were detected. A detection sensitivity of 10 genome copies per reaction was obtained with all C. trachomatis serovars as well as a representative N. gonorrhoeae control strain. Among the 223 non-gonococcal isolates, 4/11 N. mucosa and 2/42 N. subflava isolates were positive in one of the two N. gonorrhoeae targets (NG4), however the assay flagged all 6 as negative due to requirements of both NG targets being positive for the assay to display an N. gonorrhoeae positive result. Conclusion: GeneXpert ® CT/NG assay was analytically highly sensitive and specific for detection of C. trachomatis and N. gonorrhoeae, showing great promise as a POC assay. Detection of two NG targets is highly advantageous for avoiding false positive N. gonorrhoeae results.